2000
DOI: 10.1038/modpathol.3880130
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Pathology of Erdheim-Chester Disease

Abstract: Erdheim-Chester disease (ECD) is a rare non-Langerhans' cell histiocytosis that may present with pulmonary symptoms. The condition seems to be nonfamilial and typically affects middle-aged adults. Radiographic and pathologic changes in the long bones are diagnostic, but patients often present with extraskeletal manifestations. Advanced pulmonary lesions are associated with extensive fibrosis that may lead to cardiorespiratory failure. The clinical, radiologic, and pathologic features of six patients with ECD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 25 publications
2
66
0
6
Order By: Relevance
“…To our best knowledge, CD1a was uniformly negative in all cases of ECD reported to date. In ECD, the lesional cells are usually S-100 negative, although positivity has been described in previous cases in the literature and in different organs in patients with otherwise typical disease (9,11,20). The histiocytes in sinus histiocytosis with massive lymphadenopathy (Rosai-Dorfman disease) are similar to those seen in ECD, but they frequently contain intact lymphocytes (emperipolesis).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To our best knowledge, CD1a was uniformly negative in all cases of ECD reported to date. In ECD, the lesional cells are usually S-100 negative, although positivity has been described in previous cases in the literature and in different organs in patients with otherwise typical disease (9,11,20). The histiocytes in sinus histiocytosis with massive lymphadenopathy (Rosai-Dorfman disease) are similar to those seen in ECD, but they frequently contain intact lymphocytes (emperipolesis).…”
Section: Discussionmentioning
confidence: 89%
“…Orbital disease with exophthalmos and xanthoma-like lesions of the eyelid are also common (5). Pulmonary involvement is rare, but advanced lesions are associated with extensive fibrosis that can lead to cardiorespiratory failure (9,11,23). No effective treatment strategies have been described in the literature thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Although the identity of the positive cells as neoplastic or benign was difficult to determine, the expression of factor XIIIa in a subset of the histiocytes is not entirely unexpected as factor XIIIa expression has also been reported in ErdheimChester disease, a rare non-Langerhans' cell histiocytosis. 73 The significance of this finding and its possible role in the histogenesis of HSs is uncertain and requires investigation in a greater number of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Review of previous osteoarticular imaging showed classical changes of the disorder. [1][2][3] In view of the symptomatic and functional deterioration, treatment was restarted with prednisolone 40 mg plus cyclophosphamide 100 mg daily, with mesna and oral bisphosphonate prophylaxis. Over the following 6 weeks VC and TLCO improved from 2.1 to 2.8 l, and from 3.04 to 4.02 mmol/kPa/min, respectively (fig 2), with a modest improvement in exertional dyspnoea, energy, appetite and weight.…”
Section: Case Historymentioning
confidence: 99%
“…1 Symmetrical osteosclerotic lesions in the long bones, sparing the epiphyses, are virtually pathognomonic. [1][2][3] Thoracic computed tomographic (CT) appearances include reticular and centrilobular nodular opacities, scattered ground glass shadowing, and interlobular septal and pleural thickening, often with an upper zone predominance. Adenopathy is uncommon.…”
mentioning
confidence: 99%